Usage of the Healthy Eating Index-2015 (HEI-2015) (P13-031-19). (13th June 2019) - Lerman, Jennifer; Reedy, Jill; Kaefer, Christine; Pannucci, TusaRebecca; Kuczynski, Kevin; Hiza, Hazel; Subar, Amy
Abstract: Objectives: With each iteration of the Dietary Guidelines for Americans (DGA) since 2005, scientists from the U.S. Department of Agriculture and the National Cancer Institute (NCI) have updated and released a Healthy Eating Index (HEI) to measure alignment with federal dietary guidance. The HEI-2015, which includes the 13 dietary components emphasized in the 2015–2020 DGA, was released in April 2017, and details about its development, evaluation, and applications were published in September 2018. Examination of research using the HEI-2015 and resources designed to facilitate its application are critical for researchers who study dietary quality and dietary patterns and can inform key stakeholders and scientists participating in the ongoing refinement of the index and its supporting resources. Methods: To evaluate use of resources related to the HEI-2015, we reviewed Adobe Analytics reports on the NCI HEI-2015 webpages, the main website containing background and detailed information about the application HEI-2015. We searched PubMed and Google Scholar abstracts to determine the number publications (including abstracts, poster presentations, and dissertations) that used the HEI-2015. Results: In 2017–18, there were 87, 130 page views of the NCI HEI webpages, of which 9244 were unique visitors to the HEI-2015 homepage. There were 3946 unique visitors to the "Calculating HEI Scores" webpage and 2502 unique visitors to the "SAS code" page. As of January 2019, there were 35 peer-reviewed publications utilizing the HEI-2015. A Google Scholar search yielded 20 abstracts, poster presentations, and dissertations that utilized the HEI-2015. Conclusions: Usage of the latest iteration of the Healthy Eating Index, HEI 2015, has been growing in the only 20 months since its release in 2017. Publications using it include a range of topics, such as economic research, epidemiology, surveillance, and sustainability. Given the relatively small number of publications, abstracts or posters that have used the HEI-2015, and the large number of unique visitors to the HEI website, especially the SAS code webpage, many more applications of the HEI-2015 are anticipated in the near future. Funding Sources: None.